PERAN DINAS KEBUDAYAAN DAN PARIWISATA KABUPATEN REMBANG DALAM PENGEMBANGAN EKOWISATA MANGROVE PARK DESA PASAR BANGGI - Anggraini, Dina Eka; Nurcahyanto, Herbasuki; Rostyaningsih, Dewi (Journal of Public Policy and Management Review, 2024)
Mangrove Park Ecotourism in Pasar Banggi Village is a conservation-based tourist attraction in Rembang Regency. Since the Covid-19 pandemic, the existence of this tourist spot has diminished. This has also led to the neglect of the facilities. Additionally, there are other untapped potentials in the creative economy sector, which have not gained attention from the government. As the leading sector in local tourism affairs, the involvement of the Department of Culture and Tourism of Rembang Regency is needed to address the issues at hand. This study aims to describe the role of the Department of Culture and Tourism of Rembang Regency in the Development of Mangrove Park Ecotourism in Pasar Banggi Village and examine the supporting and inhibiting factors. The study utilizes Biddle and Thomas' role theory combined with Jim Ife and Frank Tesoriero's theories to delineate the role of the Department of Culture and Tourism of Rembang Regency in the development of Mangrove Park Ecotourism in Pasar Banggi Village. This research adopts a descriptive qualitative research method. The findings indicate that there are still roles that are not optimally performed, particularly in facilitative and educational roles, which are caused by role transitions and limited budgets. Recommendations include collaboration between the Department of Culture and Tourism of Rembang Regency and the Village Community Empowerment Agency to empower the communities around the Mangrove Park Ecotourism area in Pasar Banggi Village. Furthermore, cooperation with private entities such as accommodation providers can enhance the development of Mangrove Park Ecotourism in Pasar Banggi Village.